I17 Reduced rates of juvenile onset recurrent respiratory papillomatosis in australia after implementation of a national hpv vaccination program. (12th March 2018) - Zurynski, Y; Brotherton, JML; Novakovic, D; Cheng, ATL; Booy, R; Berkowitz, R; Garland, SM; Elliott, E; Black, R
Abstract : Aims: Juvenile onset Recurrent Respiratory Papillomatosis (JoRRP) is a rare chronic disease caused by human papillomavirus (HPV) types 6 and 11. Children with RRP require multiple surgical interventions; tracheostomy may be needed and sometimes the disease is fatal. Infections are now preventable through HPV vaccination. Following an extensive quadrivalent HPV vaccine catch-up program for females aged 12–26 years in 2007–2009, in Australia, we aimed to monitor the changes in incidence and demographics of JoRRP over time. Methods: The Australian Paediatric Surveillance Unit (APSU) conducted national surveillance for JRRoP using its well established reporting system. In addition to the 1450 paediatricians who report to the APSU each month, paediatric otorhinolaryngologists were also enrolled in the APSU and offered HPV typing. We report findings for the five-year period to end 2016. Results: The average annual incidence rate was 0.0715 per 1 00 000 children aged <16 years. The largest number of cases was reported in the first year, with decreasing annual frequency thereafter. The rate declined significantly from 0.163 per 1 00 000 in 2012 to 0.024 per 1 00 000 in 2016 (p=0.034). Among the 15 incident cases 60% male, 60% were first born children and 13 (87%) were born vaginally. None of the mothers of these children had received the HPV vaccine before pregnancy, and 3 (20%) of the mothers had a history of genital warts. Seven genotyped cases were positive for HPV including 4 that were HPV6 positive and 3 that were HPV11 positive. Conclusion: To our knowledge this is the first report internationally documenting decline in JoRRP incidence in children following a quadrivalent HPV vaccination program.